NIKOTIN DAN ASAM FOLAT PADA KANKER SERVIKS - Tarigan, Suci Nanda Resti; Parapat, Friska Margareth (Colostrum Jurnal Kebidanan, 2021)
Cervical cancer is a malignant tumor that grows in the servix is the lowest part of the uterus attached to the top of the vagina and usually appears in women aged 35-55 years. Causative factors of servical cancer is human pappiloma virus and a risk factor for cervical cancer is smoking and folic acid deficiency. Indonesia is one country that has a high smoking habit (4,8%). Cervical cancer death rate from cancer foundation Indonesia, each year approximately 500.000 women diagnosed with cervical cancer and over 250.000 women die from cervical cancer. Research design is cross sectional analytic approach to determine the correlation with the nicotine levels of folic acid in the mother cervical cancer. With the sample of 52 and the sampling technique by means concecutive sampling. Kolmogorov smirnov test for normality using the analysis conducted univariat and bivariat. The result showed a significant correlation strong between nicotine levels with folic acid in the mother cervical cancer with the direction of positif correlation (P<0,001). Average levels of nicotine in the mother cervical cancer was higher (20,7 ng.ml) and mean levels of folic acid in cervical cancer is low (5,7 ng.ml). Secondhand smoke is a potential in the development of cervical cancer, for it is recommended to women to keep cigarette smoke.   Keyword : Nicotine, Passive Smoker, Cervix Cancer